2020
DOI: 10.1101/2020.05.11.20096727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A one-year hospital-based prospective COVID-19 open-cohort in the Eastern Mediterranean region: The Khorshid COVID Cohort (KCC) study

Abstract: 47

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In another study, residual signs suggesting pulmonary fibrosis were found most frequently in a subgroup of critical COVID-19 patients [ 5 ]. Comparisons between ward and ICU patients did not reveal statistically significant differences regarding symptoms at three months of follow-up [ 20 ] or between severe or non-severe patients at one month of follow-up [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, residual signs suggesting pulmonary fibrosis were found most frequently in a subgroup of critical COVID-19 patients [ 5 ]. Comparisons between ward and ICU patients did not reveal statistically significant differences regarding symptoms at three months of follow-up [ 20 ] or between severe or non-severe patients at one month of follow-up [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of smoking and COVID-19 by Simons, et al found that a similar underrepresentation was apparent in seven other countries: Italy, Israel, Kuwait, Mexico, Spain, Switzerland, and the U.K. 4 They found only marginal under-representation in South Korea and a reversed pattern in Iran. Using sex-adjusted rates of smoking prevalence there was moderate under-representation of smokers in South Korea --18.5% of 28 hospitalized patients 5 vs a sexadjusted national rate of 28.6%, 6 and in Iran --14% of 490 hospitalized COVID-19 patients 7 vs. a sex-adjusted national rate of 24.6%. 8 Additionally, a small study from Germany found a smoking rate of 6% of 50 hospitalized patients 9 vs. a sex adjusted national rate of 24.9%.…”
Section: Introductionmentioning
confidence: 94%
“…Considering more comprehensive variables such as IL-6 levels, D-Dimer, and radiographic diagnosis, may yield more accurate results in the laboratory-based risk charts. Furthermore, the variability in treatment protocols across countries and individual organizations might lead to different results [22,52]. External validation of the proposed risk assessment method is the focus of our future work.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the Khorshid COVID-19 Cohort (KCC) dataset [22,34] weeks, and the first year after discharge. In total, 630 COVID-19 patients were enrolled in our study.…”
Section: Dataset and Variable Selectionmentioning
confidence: 99%
See 1 more Smart Citation